Development of a Mosque Accounting Information System (SIMAS) at the Al-Ishlah Wall Mosque Adiwerna Tegal - Mar’atusholihah, Rufaidah; Putri, Nurul wulandari (MultiTech Publisher, 2024)
Mosque finances are a phenomenon that has existed for a long time, but in the current digital era, various problems have arisen regarding reporting and transparency. The aim of this research is to design mosque financial bookkeeping based on Interpretation of Financial Accounting Standards (ISAK) 35. This research focuses on developing a mosque accounting information system that is designed in accordance with applicable accounting standards. This research is software research to develop a financial information system for the Al-Ishlah Register Lor Adiwerna Mosque. Data was collected using interview and recording techniques. This system was validated by two mosque treasurers. Data were analyzed using descriptive analysis techniques. Based on the research results, a financial information system was produced that can be used to manage mosque finances